PENGETAHUAN IBU TENTANG PEMBERIAN STIMULASI DENGAN PERKEMBANGAN MOTORIK HALUS ANAK USIA PRASEKOLAH - Siti Robiatul Adawiah; Ria Setia Sari; Febi Ratnasari (Yayasan Nusantara Hasana Berdikari, 2023)
In the age of 0-6 years or preschool age the formation of character will occur both the attitude, behavior and personality of a child. The level of mother's knowledge influences the process of providing stimulation that can increase the growth and development of children by giving love by caressing, joking and the like that is fun for children, doing varied play activities. Method: use a comprehensive strategy through the internet, in a research journal database using the help of a google search site with e-Resource access. Literature sources used in the period 2015-2020. Based on the 20 journals analyzed, there are similarities regarding the level of knowledge, role and parenting of the mother in providing stimulation to the child's fine motor development which can be concluded that knowledge and parenting in the role of the mother are interrelated because the mother as an educator must have the necessary knowledge broad in providing stimulation to the development of their children, especially in fine motor with the aim to train small muscles that will develop optimally.